Concept Image Siswa dalam Pembelajaran Matematika - Dita Oktavihari; M. Gunawan Supiarmo (FKIP Universitas Mataram, 2026)
Concept image is a mental representation that plays an important role in shaping students'conceptual understanding of mathematical concepts. The difference between concept image andconcept definition often causes misconceptions and students' difficulties in understanding andapplying mathematical concepts. This study aims to examine and synthesize research resultsregarding students' concept image in mathematics learning. The study used the SystematicLiterature Review (SLR) method by analyzing ten scientific articles published in national andinternational journals. The review process was carried out through the stages of identification,selection, evaluation, and synthesis of articles based on their suitability to the research focus. Theresults of the study indicate that students' concept images in various mathematical materials, suchas algebra, systems of linear equations in two variables, matrices, exponents, exponentialfunctions, sequences and series, quadrilaterals, and the Pythagorean Theorem, are still not fullyin line with the concept definition. This discrepancy is influenced by learning experiences, learningstrategies, mastery of prerequisite concepts, as well as didactic, epistemological, and ontogenicobstacles. In addition, procedure-oriented learning tends to produce less in-depth conceptualunderstanding than learning that emphasizes concept exploration and the use of variousmathematical representations. Therefore, mathematics learning needs to be designed to facilitatethe formation of concept images aligned with concept definitions through meaningful learningexperiences. This study is expected to serve as a reference for researchers and educators indeveloping learning strategies that support improved student conceptual understanding.